Selection of Asynchronized Turbogenerators Parameters Taking into Account the Operating Mode - Shevchenko, V. V.; Duniev, O. О.; Pototskyi, D. V. (Інститут енергетики Академії наук Молдови, 2024)
The purpose of the work is to develop an algorithm for calculating currents in the asynchronized turbogenerator rotor windings when it operates at a power system with a variable load. Typically, synchronous turbogenerators of thermal power plants are used to maintain the balance of active and reactive power in the power system. But they cannot fully ensure the maintenance of balance by switching to non-nominal modes: during periods of power consumption dips, reduce power to 50-70% and switch to under-excitation mode to compensate for reactive power. Therefore, it is promising to install asynchronized turbogenerators at power plants in parallel with synchronous turbogenerators, which remain stable over a wide range of changes in active and reactive power. The work analyzed data from the operation of asynchronous turbogenerators in different countries. The subject of the study was an ASTG-200-2U3 asynchronized turbogenerator with two identical field windings. The goal of the work was achieved by calculating the field windings currents using the finite element method and modeling in the FEMM program when the load magnitude and nature changes. The most important results of the work are the proposed algorithm for calculating the asynchronized turbogenerators field currents de pending on the load size and nature in order to maintain the frequency and voltage nominal values. The significance of the results obtained lies in the fact that practical recommendations have been obtained for choosing the asynchronized generator load angle depending on the load size and nature, including in the modes of consumption of reactive energy.
Keywords: synchronous turbogenerator; synchronous turbogenerator; the load nature; rotor winding; magnetic field modeling; turbogenerator asinhron; turbogenerator sincron; natura sarcinii; înfășurarea rotorului; modelarea câmpului magnetic